2019
DOI: 10.1016/j.ekir.2019.05.358
|View full text |Cite
|
Sign up to set email alerts
|

Sat-316 Health Related Quality of Life of Children With Nephrotic Syndrome in Lagos Nigeria

Abstract: Accumulation of ammonia in the blood may result in an acute life-threatening event in children. Patients typically present with lethargy, poor feeding, and hypotonia; if not managed efficiently, patients can develop seizures, coma, and eventually die. Management of hyperammonemia is difficult in children given the non-specific symptoms, age specific etiologies, and lack of consensus in the treatment plan. We systematically reviewed published literature to provide expert consensus panel recommendations for medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The ten selected studies consist of case–control studies (n = 5) [ 10 , 17 , 21 23 ], longitudinal cohort studies (n = 2) [ 24 , 25 ], and cross-sectional studies (n = 3) [ 15 , 16 , 26 ]. The countries of study were distributed among four continents as follows: North America [ 24 , 25 ], Europe [ 16 , 21 ], Asia [ 15 , 17 , 22 , 23 ], and Africa [ 10 , 26 ]. All the studies were hospital-based.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The ten selected studies consist of case–control studies (n = 5) [ 10 , 17 , 21 23 ], longitudinal cohort studies (n = 2) [ 24 , 25 ], and cross-sectional studies (n = 3) [ 15 , 16 , 26 ]. The countries of study were distributed among four continents as follows: North America [ 24 , 25 ], Europe [ 16 , 21 ], Asia [ 15 , 17 , 22 , 23 ], and Africa [ 10 , 26 ]. All the studies were hospital-based.…”
Section: Resultsmentioning
confidence: 99%
“…In five studies that reported sex distribution [ 15 , 17 , 22 , 24 , 26 ], the total number of males and females was 204 and 122, respectively, with an approximate ratio of 1.7: 1 (Table 1 ). Study methodological quality, using the NOS, shows a star-rating of < 7 (low quality) for three studies [ 15 , 16 , 26 ] and ≥ 7 (high quality) for seven studies [ 17 , 21 25 ]. (N/B: Rating indicates the range of quality [based on the adopted criteria from NOS] and does not translate to unreliable study findings for studies rated as low quality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is currently no disease specific HRQOL survey for children with NS. PedsQL™-4 GCS has been used on NS children from diverse populations [ 5 , 17 , 23 , 24 ], however, its trustworthiness to assess QOL in NS children was lately evaluated in a systematic review involving 10 studies which concluded that the uniformity of the assumptions across the assessed studies accentuates the reliability of non-specific QOL instruments in valuing HRQOL in those children [ 25 ]. Recently a trial to create an NS-specific QOL tool was published in 2019, assessed by 11 experts, and applied to 100 NS children [ 26 ], however, this tool is not published or authorized yet.…”
Section: Discussionmentioning
confidence: 99%